Antifungal Activity and Action Mechanism of Ginger Oleoresin Against Pestalotiopsis microspora Isolated From Chinese Olive Fruits - Chen, Tuanwei; Lu, Ju; Kang, Binbin; Lin, Mengshi; Ding, Lijie; Zhang, Lingyan; Chen, Guoying; Chen, Shaojun; Lin, Hetong (Frontiers in Microbiology, 2018)
Pestalotiopsis microspora (P. microspora) is one of dominant pathogenic fungi causing rotten disease in harvested Chinese olive (Canarium album Lour.) fruits. The purposes of this study were to evaluate the antifungal activities of ginger oleoresin (GO) against P. microspora and to illuminate the underlying action mechanisms. The in vitro assays indicate that GO exhibited strong antifungal activity against mycelial growth of P. microspore, and with 50%-inhibition concentration (EC50) and 90%-inhibition concentration (EC90) at 2.04 μL GO and 8.87 μL GO per mL propylene glycol, respectively, while the minimal inhibitory concentration (MIC) and minimal fungicidal concentration were at 10 μL GO and 30 μL GO per mL propylene glycol, respectively. Spore germination of P. microspora was inhibited by GO in a dose-dependent manner, and with 100% inhibition rate at the concentration of 8 μL GO per mL propylene glycol. Compared to the control, the cellular membrane permeability of P. microspora increased due to severe leakage of intercellular electrolytes, soluble proteins, and total sugars with the treatments (EC50, EC90) by GO during incubation. In addition, analysis of fatty acid contents and compositions in cellular membrane by GC-MS indicated that GO could significantly promote the degradation or peroxidation of unsaturated fatty acids in P. microspore, resulting in the enhancement of membrane fluidity. Moreover, observations of microstructure further showed the damage to plasma membrane and morphology of P. microspora caused by GO, which resulted in distortion, sunken and shriveled spores and mycelia of the pathogen. Furthermore, in vivo assay confirmed that over 3 MIC GO treatments remarkably suppressed disease development in P. microspore inoculated-Chinese olive fruit. These results demonstrate that owing to its strong antifungal activity, GO can be used as a promising antifungal agent to inhibit the growth of pathogenic fungi in Chinese olives.